Quản lí dạy học tiếng Anh cho sinh viên ngành Ngôn ngữ Anh ở các trường đại học khối ngành Tài chính - Ngân hàng: Thực trạng và giải pháp - Nguyễn Thị Thùy Trang, Nguyễn Thị Thùy Trang (Tạp chí Giáo dục, 2026)
Universities that offer English-major undergraduate programs are expanding their training capacity in order to meet the demand for English-proficient human resources capable of implementing foreign-invested projects as well as supporting international integration in the current socio-economic development process. However, despite notable achievements, shortcomings remain in the management of English language teaching and learning for English-major undergraduates at universities. This paper aims to investigate and assess the current situation of English language teaching and learning management for English-major students at several universities in the Finance and Banking sector, thereby proposing solutions to enhance management effectiveness in the present period. To conduct this study, the author employed three groups of research methods: theoretical research, empirical research, and expert consultation. The data used in this study were collected from annual academic reports and the author’s surveys. The research results show that the application of appropriate management measures contributes to enhancing transparency, operational efficiency, and the level of compliance with the program’s learning outcomes standards.